An innovative blended educational learning and augmented traning approach (BELATA) for engineering and conational education - Mathai, K. James (Indian Journal of Training and Development)
Due to the Industrial Revolution (IR-04), the technologies are extensively used globally because of their potential to increase productivity, in almost all engineering industries, business establishments, etc. The cutting-edge tec.- Reproduced
Keywords: Blended educational learning, Augmented training approach, BELATA, Virtual reality (VR), Augmented reality (AR), Blended learning, Flipped learning, Industry revolution 4.0 (IR-4.0), Academic education 4.0 (AE-4.00), Generation Z